2012
DOI: 10.1016/j.jep.2012.01.041
|View full text |Cite
|
Sign up to set email alerts
|

In-silico studies in Chinese herbal medicines’ research: Evaluation of in-silico methodologies and phytochemical data sources, and a review of research to date

Abstract: The available databases that catalogue information on traditional Chinese medicines are reviewed in terms of their content and utility for in-silico research on Chinese herbal medicines, as too are the various protein database resources, and the software available for use in such studies. The software available for bioinformatics and 'omics studies of Chinese herbal medicines are summarised, and a critical evaluation given of the various in-silico methods applied in screening Chinese herbal medicines, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 77 publications
0
35
0
1
Order By: Relevance
“…WP4 and WP5 contribute three papers, one focussing on in silico studies of CHM, another on in vitro and in vivo studies of CHM using an omics approach and the third on animal studies of CHM. The former offers a state-of-the-art critical review of the available TCM databases, in terms of their contents and utility for in silico research on CHM, and provides recommendations for future in silico studies of CHM (Barlow et al, 2012). The second paper is a collaboration between WP4 and WP5 members.…”
Section: Wp4 and Wp5mentioning
confidence: 99%
“…WP4 and WP5 contribute three papers, one focussing on in silico studies of CHM, another on in vitro and in vivo studies of CHM using an omics approach and the third on animal studies of CHM. The former offers a state-of-the-art critical review of the available TCM databases, in terms of their contents and utility for in silico research on CHM, and provides recommendations for future in silico studies of CHM (Barlow et al, 2012). The second paper is a collaboration between WP4 and WP5 members.…”
Section: Wp4 and Wp5mentioning
confidence: 99%
“…21 In this study, 139 constituents of the four anti-infection medicinal plants were identified using the TCM Database@Taiwan. 22 Molecular docking was used to investigate their binding affinities to the two common MRSA inhibitory targets, Penicillin binding proteins 2a (PBP2a) and 4 (PBP4).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of 200,000 natural products in plant species have been revised upward as mass spectrometry techniques have developed [3]. New databases, omics methods, and good practice standards are promising to deliver many new medicines based on plant natural products [4]. …”
Section: Introductionmentioning
confidence: 99%